2021
DOI: 10.1021/acs.orglett.1c02405
|View full text |Cite
|
Sign up to set email alerts
|

ZnI2-Directed Stereocontrolled α-Glucosylation

Abstract: Here we report a glucosylation strategy mediated by ZnI2, a cheap and mild Lewis acid, for the highly stereoselective construction of 1,2-cis-O-glycosidic linkages using easily accessible and common 4,6-O-tethered glucosyl donors. The versatility and effectiveness of the α-glucosylation strategy were demonstrated successfully with various acceptors, including complex alcohols. This approach demonstrates the feasibility of the modular synthesis of various α-glucans with both linear and branched backbone structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…Indeed, we have successfully developed a ZnI 2 -directed general strategy for 1,2-cisglucosylation bearing a 4,6-naphthylidene moiety with excellent stereoselectivity (Figure 1c). 9 In this context, confirming the wide applicability of ZnI 2 -promoted glycosylation methodology to 4,6-tether-protected glucose donors and referring to the observations in our previous experiments on mannose donors aforementioned, we envisioned that the ZnI 2 -promoted 1,2-cis-glycosylation reaction could be extended to the mannosyl trichloroacetimidate donors, promising an alternative β-mannosylation methodology without the formation of a mannosyl triflate intermediate (Figure 1d). 10 ■ RESULTS AND DISCUSSION…”
Section: ■ Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…Indeed, we have successfully developed a ZnI 2 -directed general strategy for 1,2-cisglucosylation bearing a 4,6-naphthylidene moiety with excellent stereoselectivity (Figure 1c). 9 In this context, confirming the wide applicability of ZnI 2 -promoted glycosylation methodology to 4,6-tether-protected glucose donors and referring to the observations in our previous experiments on mannose donors aforementioned, we envisioned that the ZnI 2 -promoted 1,2-cis-glycosylation reaction could be extended to the mannosyl trichloroacetimidate donors, promising an alternative β-mannosylation methodology without the formation of a mannosyl triflate intermediate (Figure 1d). 10 ■ RESULTS AND DISCUSSION…”
Section: ■ Introductionsupporting
confidence: 81%
“…We started testing the idea by subjecting a 4,6- O -tether-protected mannosyl trichloroacetimidate donor 1a (Scheme S1) to ZnI 2 -promoted glycosylation reaction with a model acceptor 2a under our developed ZnI 2 -promoted glucosylation reaction conditions and delighted in successfully attaining the desired glycosylation product 3a in 75% yield with exclusive β-stereoselectivity as expected. Results of solvent screening with ZnI 2 employed as the promoter in our previous work revealed that glycosylation reactions performed in toluene and diethyl ether (Et 2 O) afforded the 1,2- cis -glycoside products with even higher cis -selectivity than the reactions performed in dichloromethane, whereas glycosylation reactions in acetonitrile and tetrahydrofuran afforded less, presumably due to the poor solubility of ZnI 2 in these solvents. We then explored immediately the scope of acceptors on the ZnI 2 -promoted β-mannosylations and found it to be comparable to that of the glucose donors reported previously (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…Based on basic observations, the solvent effect [174][175][176][177][178][179][180], the concentration effect [181][182][183][184][185], and other factors [186][187][188], including a very recent approach using an S N 2-predicting, leaving group enhanced by a coordinating acceptor [189,190], were also accepted as factors for the stereoselectivity of glycosylation. This review focuses on two effective and stereoselective methods for glucan synthesis: the use of C2-o-tosylamide (TsNH)-benzyl (TAB) ether for bimodal glycosylation [191][192][193] and ZnI 2 -mediated 1,2-cis glycosylation [194].…”
Section: 2-cis Glycosylationmentioning
confidence: 99%
“…It has been observed that the Zn 2+ cation not only activates the donor leav-ing group but also coordinates with oxygens at the 2-and 3-positions to induce the effective interaction of TAB with an incoming nucleophile during 1,2-cis-β-mannosylation [214]. Combined with the enhancement of the fixed conformation of the pyranose ring by the 4,6-O-cyclic protection reported by Crich [244,245], a simple ZnI 2 -mediated procedure involving activation and direction to control the stereoselectivity for glucosylation has been developed as a novel general synthetic strategy for the construction of α-glucoside as one of the most abundant 1,2-cis-glycosidic bonds in nature [194]. To the best of our knowledge, the effective use of ZnI 2 for 1,2-cis glycosylation using a simple trichloroacetimidate donor has not been reported until recently.…”
Section: Zni 2 -Mediated 12-cis α-Glucosylationmentioning
confidence: 99%
“…For example, the challenging 1,2- cis linkages could be constructed by various elegant strategies, including C2 chiral auxiliaries, intramolecular aglycone delivery (IAD), hydrogen bond-mediated aglycone delivery (HAD), gold-catalyzed glycosylation explored by the Yu group, conformational restriction control, remote anchimeric assistance, , etc. In addition, solvent- or reagent-controlled stereoselective glycosylation, organic molecules, or some transition metal-catalyzed methods were also developed for 1,2- cis glycosylation. Although the state-of-the-art methods largely facilitate the construction of glycosides, overdependence on protecting group strategies may decrease the efficiency of oligosaccharide synthesis.…”
mentioning
confidence: 99%